Seni Perubatan Alternatif Di Malaysia: Analisis Permasalahan Metode Rawatan: The Art of Alternative Medicine in Malaysia: An Analysis on Treatment Methods - Mohd Farhan Md Ariffin; Khadher Ahmad; Nor Izati Samsudin; Mohamad Zaim Isamail; Muhammad Ikhlas Rosele (Global Journal Al-Thaqafah, 2024)
Alternative medical centres based on Islamic and traditional practices have expanded and flourished in Malaysia. This is due to massive response from Malaysian community towards alternative treatment in Malaysia. This is especially evident for diseases which could not be cured by the hospital and health clinic or for patients who have lost hope. Based on observation, eventhough there is significant interest among the community to find cure through alternative medical centres, there still exist many problems and questions that need effective solutions. The alternative medical field is like a slippery road in which a wrong move will lead to deviation from the truth. Hence, this research will identify as much as possible problems related to the methods of alternative treatment which consist of wrong practices and doubtful techniques practised by alternative medical centres in Malaysia and then discuss its legality or validity according to Al-Quran and Prophetic Tradition. The main methodology used in this research was an analysis on seventy (70) alternative medical centres, whether Islamic or traditional. It also includes library research to find the validity of the alternative treatment techniques discussed in this paper as guidance to all concerned.